Current Bacterial Gene Encoding Capsule Biosynthesis Protein CapI Contains Nucleotides Derived from Exonization. (January 2016) - Wang, Yong; Tao, Xia-Fang; Su, Zhi-Xi; Liu, A-Ke; Liu, Tian-Lei; Sun, Ling; Yao, Qin; Chen, Ke-Ping; Gu, Xun
Since the proposition of introns-early hypothesis, although many studies have shown that most eukaryotic ancestors possessed intron-rich genomes, evidence of intron existence in genomes of ancestral bacteria has still been absent. While not a single intron has been found in all protein-coding genes of current bacteria, analyses on bacterial genes horizontally transferred into eukaryotes at ancient time may provide evidence of intron existence in bacterial ancestors. In this study, a bacterial gene encoding capsule biosynthesis protein CapI was found in the genome of sea anemone, Nematostella vectensis. This horizontally transferred gene contains a phase 1 intron of 40 base pairs. The nucleotides of this intron have high sequence identity with those encoding amino acids in current bacterial CapI gene, indicating that the intron and the amino acid-coding nucleotides are originated from the same ancestor sequence. Moreover, 5'-splice site of this intron is located in a GT-poor region associated with a closely following AG-rich region, suggesting that deletion mutation at 5'-splice site has been employed to remove this intron and the intron-like amino acid-coding nucleotides in current bacterial CapI gene are derived from exonization. These data suggest that bacterial CapI gene contained intron(s) at ancient time. This is the first report providing the result of sequence analysis to suggest possible existence of spliceosomal introns in ancestral bacterial genes. The methodology employed in this study may be used to identify more such evidence that would aid in settlement of the dispute between introns-early and introns-late theories.